Academic rankings with RePEc - Christian Zimmermann (Econometrics, 2013)
This article describes the data collection and use of data for the computation of rankings within RePEc (Research Papers in Economics). This encompasses the determination of impact factors for journals and working paper series, as well as the ranking of authors, institutions, and geographic regions. The various ranking methods are also compared, using a snapshot of the data.
Keywords: 330; economics; bibliometrics; RePEc; ranking economists; ranking research institutions; ranking journals; ranking articles